Extreme leukocytosis and leukemoid reaction associated with the lung sarcomatoid carcinoma: an unusual case report - Wang D; Zhang H; Yu F; Fang B (International Journal of General Medicine, 2016)
Danyang Wang, Haiyan Zhang, Fengkuan Yu, Baijun Fang Department of Hematopathy, The Affiliated Cancer Hospital of Zhengzhou University, Zhengzhou, People’s Republic of China Purpose: To report a rare case of extreme leukocytosis and leukemoid reaction associated with lung sarcomatoid carcinoma (LSC) and increase people’s awareness of the disease. Patients and methods: A 58-year-old male patient was diagnosed with LSC; however, after the end of the second course of chemotherapy, his white blood cells increased gradually without fever or use of medications such as granulocyte colony-stimulating factor and steroids. A bone marrow biopsy then confirmed it to be a leukemoid reaction. Results: The patient died of multiple organ failure 2 months after being diagnosed with leukocytosis. Conclusion: LSC associated with leukemoid reaction is very rare and the prognosis is poor. When a patient’s white blood cells are extremely elevated, we should think of the possible causes of the tumor itself and identify it with other diseases. However, more data and evidence are still needed to find an effective adjuvant therapy for these patients. Keywords: lung sarcomatoid carcinoma, leukemoid reaction